Education in precarious times: a comparative study across six countries to identify design priorities for mobile learning in a pandemic. Issue 5 (25th June 2020) - Hall, Tony; Connolly, Cornelia; Ó Grádaigh, Seán; Burden, Kevin; Kearney, Matthew; Schuck, Sandy; Bottema, Jeroen; Cazemier, Gerton; Hustinx, Wouter; Evens, Marie; Koenraad, Ton; Makridou, Eria; et al.
Abstract : Purpose: This paper is based on the emergency changes we have had to make in the European DEIMP Project (2017-2020), "Designing and Evaluating Innovative Mobile Pedagogies" (DEIMP). DEIMP is undertaken by a transnational consortium comprising partner institutions and schools from the UK (coordinating), Australia, Belgium, Cyprus, Ireland and The Netherlands. As well as the enforced changes to the project, there have been major adjustments in how education is being provided in each of our countries, across all sectors: primary, secondary and tertiary. The purpose of this paper is to provide pragmatic guidelines that will help us respond effectively in the uncertain present, and plan systematically for an unpredictable, post-pandemic future. Design/methodology/approach: The authors outline 21 design principles underpinning innovative mobile learning, which will be of pragmatic use to all using mobile learning in the COVID-19 pandemic. These principles have emerged in the context of the three-year European DEIMP Project (2017-2020). The authors also examine major educational changes that have recently been imposed upon teachers and educational researchers, and key aspects of the current emergency response in education internationally, and resultant implications for educational technology and mobile learning. Findings: A living record highlighting what is currently happening in the educational systems of the DEIMP project's respective partner countries. The paper outlines design concerns and issues, which will need to be addressed as the authors endeavour to bridge both the digital divide and digital use divide in remote education. Furthermore, the paper illustrates 21 pragmatic design principles underpinning innovative mobile pedagogies. Originality/value: A comparative study of the effects of the pandemic across six countries, including The UK, Australia, Belgium, Cyprus, Ireland and The Netherlands. The authors outline 21 design principles for mobile learning, which is hoped will help us respond effectively in the uncertain present, and plan systematically for an unpredictable, post-pandemic future.